Analisis Kesenjangan Penerapan ISO 45001:2018 pada Perusahaan Makanan Ringan - Berta Sylviani Br Ginting; Tatan Sukwika; Marningot T. Natalis Situmorang (Jurnal Ekologi, Masyarakat dan Sains, 2022)
Snack company is committed to implementing an occupational safety and health system (SMK3)based on ISO 45001:2018. Therefore, an analysis of the preparation of ISO 45001:2018 was carried out to determine the company's preparation in implementing ISO 45001:2018. The purpose of the research is to measure the efforts that have been designed and implement the SMK3 design based on ISO 45001:2018 carried out by snack company and measure the suitability of the initial conditions based on ISO 45001:2018. Data analysis was carried out using a Likert scale using the Spearman correlation test. The results of the fulfillment of SMK3 preparation based on ISO 45001:2018 obtained an Organizational Context clause of 50%, a Leadership, and Employee Participation clause 62.5%, a Planning clause 72.5%, a Support clause 89%, an Operational clause 73%, a Performance Evaluation clause 92% and an increase clause 87%. The results of the reliability test of the Cronbach Alpha value above 0.70, the Spearman correlation test with a significant value of 0.985. The conclusion that can be drawn is that the company for most or above 50% has implemented the ISO 45001:2018 scheme. The clauses that have been mostly implemented are planning, Support, Operations, Performance Evaluation, and Improvement Clauses. While the clauses that are not implemented are the clauses of Organizational Context and Leadership and employee Participation. In conformity with the preparation of ISO 45001:2018 with the initial conditions of the company, it shows a good condition of conformity, which is 73.33%.